Nanotechnology in paper and wood engineering : fundamentals, challenges and applications - Bhat, Rajeev; Kumar, Ashok (Professor of microbial biotechnology); Nguyễn, Tuấn Anh; Sharma, Swati (Elsevier, 2022)
Nanotechnology in Paper and Wood Engineering: Fundamentals, Challenges and Applications describes recent advances made in the use of nanotechnology in the paper and pulp industry. Various types of nano-additives commonly used in the paper industry for modification of raw material to enhance final products are included, with other sections covering the imaging applications of nano-papers and nano-woods in pharmaceuticals, biocatalysis, photocatalysis and energy storage. This book is an important reference source for materials scientists and engineers who are looking to understand how nanotechnology is being used to create more efficient manufacturing processes in for the paper and wood industries.
Keywords: Paper industry -- Technological innovations.; Pulpwood industry -- Technological innovations.; Nanotechnology.; elektronické knihy; electronic books